Medieval Days - Brimax Publishing (Brimax Publishing, 2008)
Welcome to the castle! The lord and lady are holding a party in the Great Hall. The jesters are juggling and the guests are eating with their fingers. Tomorrow the knights will put on their armour and the battle will begin. Where are you? you've travelled back in time to medieval days.
Keywords: Who We Are -- -Global Citizens